Developing a framework for integrating health equity into the learning health system. Issue 3 (26th June 2017) - Brooks, Danielle; Douglas, Megan; Aggarwal, Neelum; Prabhakaran, Shyam; Holden, Kisha; Mack, Dominic
Abstract: While there have been gains in the overall quality of health care, racial and ethnic disparities in health outcomes continue to persist in the United States. The Learning Health System (LHS) has the potential to significantly improve health care quality using patient‐centered design, data analytics, and continuous improvement. To ensure that health disparities are also being addressed, targeted approaches must be used. This document sets forth a practical framework to incorporate health equity into a developing LHS. Using a case study approach, the framework is applied to 2 projects focused on the reduction of health disparities to highlight its application.